Surgical challenges in fibroid uterus - case series - Vijay Y Kalyankar; Bhakti Vijay Kalyankar; Srinivas N Gadappa; Revati Rameshwar Ghayal (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: It is an art and skill to surgically remove large and difficult fibroid & hysterectomies. This case series mentions variety of fibroids at different ages including pregnancy & numerous ways of surgically handling them successfully. Objectives: To study various surgical challenges and ways to overcome them in fibroids. Method: Total 10 cases with challenging surgeries were studied at Govt Medical College Hospital, Aurangabad from May 2018 to May 2019. Demographic details, presenting complaints, clinical examination findings, imaging techniques, investigations and operative difficulties and measures to prevent complications were studied. Results: Some presurgical techniques like preoperative use of GNRH analogue, preoperative stenting of ureter, anaemia correction and intraoperative techniques like hemi section of uterus, enucleating the fibroid using correct surgical plane, identifying ureter and surgical expertise helped to avoid all complications in surgery. Conclusions: Knowledge of altered anatomical structures, meticulous surgery by an expert following all surgical principles in fibroid surgery prevent injuries to the urinary tract, reduce blood loss and make surgery successful.